Nuclear structure in China 2010 : proceedings of the 13th National Conference on Nuclear Structure in China, Chi-Feng, Inner Mongolia, China, 24-30 July 2010 - Bai, Hong-Bo (World Scientific, 2011)
This volume is a collection of the contributions to the 13th National Conference on Nuclear Structure in China (NSC2010). It provides an important updated resource in the nuclear physics literature for researchers and graduate students studying nuclear structure and related topics. Recent progress made in the study of exotic nuclear structure, the structure and synthesis mechanism of superheavy nuclei, nuclear astrophysics, and the development of quantum many body approaches are covered.